For this case we must solve the following system of equations:
We clear "x" from the second equation:
We substitute in the first equation:
We look for the value of the variable "x":
Thus, the solution of the system is given by:
Answer:
Solution: { -29/3 , -10/3 }
Explanation:
2y = x + 3 ---------> equ 1
5y = x - 7 equ 2
equ 1 - equ s ====> -3y = 10
y = -10/3
Put y = -10/3 in equ 1
2 * (-10/3) = x + 3
-20/3 = x + 3
(-20/3) - 3 = x
(-20/3) - (9/3) = x
(-20 - 9) / 3 =x
x = -29/3
6.0m questions
7.8m answers